“Quod Deus Coniunxit, Homo Non Separet”: Perkawinan Katolik yang Tak Terputuskan dalam Bingkai Pertanggungjawaban Yuridis-Teologis - Rikardus Jehaut (STIPAS St. Sirilus Ruteng, 2021)
This article is primarily focused on the teaching of the Catholic Churchon the doctrine of indissolubility of marriage. The principal objective isto defend the teaching by offering some canonical-theological analysisbased on canonical scripture and sacred tradition as interpretedauthoritatively by the magisterium of the Catholic church. To achievethis objective, the article is developed in three parts. The first, serves asa point of departure, examines some critics poised by some scholars onthe Church’s teaching on indissolubility of marriage. They offer severalconsiderations that suggest the teaching on indissolubility ought tobe revised in order to admit of exceptions even in case of ratum etconsummatum unions. The second part deals with the analysis of theirargument and shows their erroneous conception of the matrimonialbond. The third part provides some magisterial intervention concerningthe Church’s teaching on indissolubility. The author argues that theteaching cannot be changed since it constitutes an irreformable dogmaof faith, rooted in Sacred Scripture and flows from the very nature ofmarriage as created by God. It must be also defended for the sake of thefaithful whose faith is under constant challenge by divorce mentalitywhich is quickly spreading to other parts of the world.